A intervenção da terapia ocupacional junto à paciente com câncer de mama: uma revisão integrativa da literatura - ALENCAR, Antonio Lukas Correa de (2023)
Cancer is the name given to several diseases that have as common characteristic the abnormal growth of cells, invade tissues and organs, and can spread to other parts of the body, causing metastasis. Cells divide rapidly, tending to be very aggressive and uncontrollable, thus causing tumors to form. Breast cancer is a disease that often affects women aged between 50 and 69 years, and can be classified according to staging, extension in lymph nodes or invasion into adjacent tissues. Thus, in view of the aspects related to women affected with breast cancer, it is the role of occupational therapists to promote conditions for the exercise of occupations that these women have previously performed. Therefore, this research aimed to analyze scientific evidence available in the literature on the role of Occupational Therapy in the treatment of women with breast cancer in the last 10 years, having as a guiding question "What scientific knowledge has been produced in the last 10 years related to the intervention of occupational therapists with patients diagnosed with breast cancer?”. An integrative literature review was carried out, in which studies will be searched in the following databases: LILACS; Scientific Electronic Library Online; PUBMED; Brazilian Journal of Occupational Therapy; Revista de Terapia Ocupacional da Universidade de São Paulo that have been published in the last 10 years. 98 studies were found, leaving only 9 that met the inclusion criteria, having been carried out with women diagnosed with breast cancer; written by occupational therapists; address occupational therapeutic interventions; published in Portuguese, Spanish or English carried out in the last 10 years. After being carefully analyzed, two categories of the most discussed topics were created: "Occupational Therapy in the physical rehabilitation of women with breast cancer" and "Occupational Therapy in the ADL's and IADL's of women with breast cancer". This integrative literature review allowed us to conclude that the role of Occupational Therapy with women with breast cancer is wide, promoting social reintegration, functionality and independence.